Resilience among higher education students in mandatory preventive social distance during the Covid-19 pandemic (Research, Society and Development, 2022)
The panorama of the pandemic that afflicts the world since the first quarter of 2020 by the pathogenic agent coronavirus (Covid-19). The research aimed to measure the resilience scores among academics, from Higher Education, in mandatory preventive social distancing the Covid-19 pandemic. Quantitative exploratory study, carried out from November 2021 to April 2022. There were 85 academics from different areas of higher education institutions, aged between 18 and 47 years. Among the students, 32.9% were female and 76.1% were male. The instruments for data collection were: a questionnaire with sociodemographic data and the Resilience Scale (ER). The results show a higher prevalence in females to a moderately high resilience, in relation to males. We can say that at ages under 20, resilience remains low, being moderately high at ages 26 to over 30 years. Religious practice regarding the high level of resilience, which can be observed among Catholics, Evangelicals and Spiritists, also stands out in the high resilience parameters. It is noticed that the level of resilience can vary mainly in humanities and exact courses there is a very high resilience. Health courses showing a moderately high resilience rate of 14.1%. The courses in the area of Exact Sciences have shown a high resilience compared to other courses, with a percentage of 10.6%. It is necessary to implement student policies that promote mental health and psychological care.